Geophysical Observations of Taliks Below Drained Lake Basins on the Arctic Coastal Plain of Alaska. Issue 3 (24th March 2021) - Rangel, R. C.; Parsekian, A. D.; Farquharson, L. M.; Jones, B. M.; Ohara, N.; Creighton, A. L.; Gaglioti, B. V.; Kanevskiy, M.; Breen, A. L.; Bergstedt, H.; Romanovsky, V. E.; Hinkel, K. M.
Abstract: Lakes and drained lake basins (DLBs) together cover up to ∼80% of the western Arctic Coastal Plain of Alaska. The formation and drainage of lakes in this continuous permafrost region drive spatial and temporal landscape dynamics. Postdrainage processes including vegetation succession and permafrost aggradation have implications for hydrology, carbon cycling, and landscape evolution. Here, we used surface nuclear magnetic resonance (NMR) and transient electromagnetic (TEM) measurements in conjunction with thermal modeling to investigate permafrost aggradation beneath eight DLBs on the western Arctic Coastal Plain of Alaska. We also surveyed two primary surface sites that served as nonlake affected control sites. Approximate timing of lake drainage was estimated based on historical aerial imagery. We interpreted the presence of taliks based on either unfrozen water estimated with surface NMR and/or TEM resistivities in DLBs compared to measurements on primary surface sites and borehole resistivity logs. Our results show evidence of taliks below several DLBs that drained before and after 1949 (oldest imagery). We observed depths to the top of taliks between 9 and 45 m. Thermal modeling and geophysical observations agree about the presence and extent of taliks at sites that drained after 1949. Lake drainage events will likely become more frequent in the future due to climate change and our modeling results suggest that warmer and wetter conditions will limit permafrost aggradation in DLBs. Our observations provide useful information to predict future evolution of permafrost in DLBs and its implications for the water and carbon cycles in the Arctic. Key Points: Geophysical soundings indicate that sublake taliks are partially refrozen in basins that drained before and after 1949 Geophysical and talik refreeze modeling results agree on the presence of remnant sublake taliks Complete lake drainage results in faster talik refreezing rate than partial drainage